Efectos del programa CIPRES sobre el riesgo suicida en adolescentes - Bahamón, Marly J.; Alarcón-Vásquez, Yolima; Trejos-Herrera, Ana M.; Vinaccia, Stefano; Cabezas Corcione, Andrés; Sepúlveda-Aravena, Joaquín (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: Effects of the CIPRES program on suicidal risk in adolescents. The objective of the study was to evaluate the specific changes generated by the CIPRES program on suicidal risk in adolescents. The sample comprised 106 adolescents aged between 13 and 18 years old (53 in the experimental group, 53 in the control group), of which 54.7% were women (n = 58). The study used a quasi-experimental design of repeated pretest-posttest measures with a control group. Two assessment instruments were administered before and after the program: The Scale of the Suicide Risk (ERS) and the Inventory of Positive and Negative Suicidal Ideation (PANSI). The pretest-posttest ANCOVAs showed that the program significantly reduced (p < .05) the scores of suicidal ideation, planning, self-harm, isolation/social support, lack of family support, and global suicide risk. In addition, it significantly increased positive ideation scores. The results support the relevance of this program to reduce suicidal risk in adolescents. Keywords: CIPRES; suicide risk; adolescents; psychological intervention; quasi-experiment. Resumen: El estudio tuvo por objetivo evaluar los cambios específicos generados por el programa CIPRES sobre el riesgo suicida en adolescentes. La muestra se configuró con 106 adolescentes entre los 13 y 18 años (53 experimentales, 53 controles), de los cuales el 54.7% eran mujeres (n = 58). El estudio utilizó un diseño cuasi-experimental de medidas repetidas pretest-postest con grupo de control. Se administraron dos instrumentos de evaluación antes y después de la aplicación del programa: la Escala de Riesgo Suicida (ERS) y el Inventario de Ideación Suicida Positiva y Negativa (PANSI). Los ANCOVAs pretest-postest evidenciaron que el programa redujo significativamente (p < .05) las puntuaciones en ideación suicida, planificación, autolesión, aislamiento/soporte social, falta de apoyo familiar, y riesgo suicida global. Además, aumentó significativamente las puntuaciones en ideación positiva. Los resultados apuntan a la relevancia de este programa para reducir el riesgo suicida en adolescentes. Palabras clave: CIPRES; riesgo de suicidio; adolescentes; intervención psicológica; cuasiexperimento.